The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1029/2019jg005109
|View full text |Cite
|
Sign up to set email alerts
|

The Budget of Macrobenthic Reworked Organic Carbon: A Modeling Case Study of the North Sea

Abstract: The importance of macrobenthos in benthic‐pelagic coupling and early diagenesis of organic carbon has long been recognized but has not been quantified at a regional scale. By using the southern North Sea as an exemplary area we present a modeling attempt to quantify the budget of total organic carbon (TOC) reworked by macrobenthos in seafloor surface sediments. Vertical profiles in sediments collected in the field indicate a significant but nonlinear correlation between TOC and macrobenthic biomass. A mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(61 citation statements)
references
References 83 publications
5
56
0
Order By: Relevance
“…However, few included dynamic benthic ecological elements, specifically coupling biogeochemical fluxes and microbes (Yakushev et al, 2017), or feedbacks between OC supply and macrofaunal biomass (Ehrnsten et al, 2019) and their responses to hypoxia and nutrient loading (Soetaert and Middelburg, 2009). Furthermore, ecosystem models only recently linked macrofaunal dynamics to changes in biological transport and their effects on biogeochemical fluxes (Daewel and Schrum, 2013;Butenschön et al, 2016;Zhang and Wirtz, 2017), inducing strong temporal dynamics resulting from high sensitivity to environmental drivers (Timmermann et al, 2012;Ehrnsten et al, 2019;Zhang et al, 2019). The major limitation of such coastal ecosystem models rests in their highly simplified representation of the vertical sedimentary structure, which cannot resolve strong biogeochemical and biological spatial gradients with sediment depth.…”
Section: Modeling "Transient" Carbon Cyclingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, few included dynamic benthic ecological elements, specifically coupling biogeochemical fluxes and microbes (Yakushev et al, 2017), or feedbacks between OC supply and macrofaunal biomass (Ehrnsten et al, 2019) and their responses to hypoxia and nutrient loading (Soetaert and Middelburg, 2009). Furthermore, ecosystem models only recently linked macrofaunal dynamics to changes in biological transport and their effects on biogeochemical fluxes (Daewel and Schrum, 2013;Butenschön et al, 2016;Zhang and Wirtz, 2017), inducing strong temporal dynamics resulting from high sensitivity to environmental drivers (Timmermann et al, 2012;Ehrnsten et al, 2019;Zhang et al, 2019). The major limitation of such coastal ecosystem models rests in their highly simplified representation of the vertical sedimentary structure, which cannot resolve strong biogeochemical and biological spatial gradients with sediment depth.…”
Section: Modeling "Transient" Carbon Cyclingmentioning
confidence: 99%
“…The major limitation of such coastal ecosystem models rests in their highly simplified representation of the vertical sedimentary structure, which cannot resolve strong biogeochemical and biological spatial gradients with sediment depth. Recent explicit representations of organism-sediment interactions as a function of depth in sediment cores (Zhang et al, 2019) nonetheless link dynamics to local macrobenthic biomass and food resources, both of which may vary temporally and spatially.…”
Section: Modeling "Transient" Carbon Cyclingmentioning
confidence: 99%
See 1 more Smart Citation
“…Mérillet et al [16] observed that bioturbation could lead to a lower persistence of TM. In general, bioturbation is higher in muddy than in sandy sediments [63], therefore, bioturbation is likely not a significant controlling factor for the preservation of TM in the three study sites, where sediments are mainly made by sand with a very low mud content. However, in their model, Zhang et al [63] described a pattern of increased bioturbation activity at Dogger Bank during summer.…”
Section: Persistence Of Trawl Marks and Signs Of Degradationmentioning
confidence: 84%
“…In general, bioturbation is higher in muddy than in sandy sediments [63], therefore, bioturbation is likely not a significant controlling factor for the preservation of TM in the three study sites, where sediments are mainly made by sand with a very low mud content. However, in their model, Zhang et al [63] described a pattern of increased bioturbation activity at Dogger Bank during summer. As a consequence, the TM at the DB site should be less stable during summer months, which is in contrast with the highest TBB mark densities recorded in that period in our datasets.…”
Section: Persistence Of Trawl Marks and Signs Of Degradationmentioning
confidence: 84%